Transitional justice in the Asia-Pacific / edited by Renée Jeffery, Hun Joon Kim. - Jeffery, Renée; Kim, Hun Joon, 1975- (Cambridge University Press, 2014)
How to address the human rights violations of previous regimes and past periods of conflict is one of the most pressing questions facing governments and policy makers today. New democracies and states in the fragile post-conflict peace-settlement phase are confronted by the need to make crucial decisions about whether to hold perpetrators of human rights violations accountable for their actions and, if so, how to best achieve that end. This is the first book to examine the ways in which states and societies in the Asia-Pacific region have navigated these difficult waters. Drawing together several of the world's leading experts on transitional justice with Asia-Pacific regional and country specialists it provides an overview of the processes and practices of transitional justice in the region as well as detailed analysis of the cases of Cambodia, Sri Lanka, Aceh, Indonesia, South Korea, the Solomon Islands and East Timor.